Keratinocyte overexpression of IL-17C promotes psoriasiform skin inflammation - Johnston, Andrew (2013)
IL-17C is a functionally distinct member of the IL-17 family that binds IL-17RE/A to promote innate defense in epithelial cells and regulate Th17 cell differentiation. We demonstrate that IL-17C (not IL-17A) is the most abundant IL-17 isoform in lesional psoriasis skin (1058pg/ml vs. 8pg/ml; p<0.006) and localizes to keratinocytes (KCs), endothelial cells (ECs) and leukocytes. ECs stimulated with IL-17C produce increased TNFα and KCs stimulated with IL-17C/TNFα produce similar inflammatory gene response patterns as those elicited by IL-17A/TNFα, including increases in IL-17C, TNFα, IL-8, IL-1α/β, IL-1F5, IL-1F9, IL-6, IL-19, CCL20, S100A7/A8/A9, DEFB4, LCN2 and PI3 (p<0.05); indicating a positive pro-inflammatory feedback loop between the epidermis and ECs. Psoriasis patients treated with etanercept rapidly decrease cutaneous IL-17C levels, suggesting IL-17C/TNFα-mediated inflammatory signaling is critical for psoriasis pathogenesis. Mice genetically engineered to overexpress IL-17C in KCs develop well-demarcated areas of erythematous, flakey “involved” skin adjacent to areas of normal appearing “uninvolved” skin despite increased IL-17C expression in both areas (p<0.05). Uninvolved skin displays increased angiogenesis and elevated S100A8/A9expression (p<0.05) but no epidermal hyperplasia; whereas involved skin exhibits robust epidermal hyperplasia, increased angiogenesis and leukocyte infiltration and upregulated TNFα, IL-1α/β, IL-17A/F, IL-23p19, VEGF, IL-6 and CCL20 (p<0.05) suggesting that IL-17C, when coupled with other pro-inflammatory signals, initiates the development of psoriasiform dermatitis. This skin phenotype was significantly improved following 8 weeks of TNFα inhibition. These findings identify a role for IL-17C in skin inflammation and suggest a pathogenic function for the elevated IL-17C observed in lesional psoriasis skin.